Investigations on the structural, electrical, magnetic and 57Fe Mössbauer studies of YFeO3. Issue 5 (1st March 2023) - Padmasree, G.; Kumar, N. Pavan; Abhinav, E. Meher; Reddy, P. Yadagiri; Reddy, Ch Gopal
Abstract: Yttrium iron oxide (YFeO3 ) sample is prepared by sol-gel method. X-ray diffraction (XRD) graph shows highly defined peaks showing that the compound possess crystalline nature. The Rietveld refined XRD data revealed that the sample has orthorhombic structure with P bnm space group. The experimental data of structural parameters is in accordance with DFT calculated theoretical structural parameters.Fourier Transform Infrared Spectroscopy (FTIR) shows that a pure phase of YFeO3 isbeen formed. Scanning electron micrograph of YFeO3 reveals that the sample has non uniform grain structure with slight porosity in it. The grains have an average grain size of about 200 nm. Raman spectroscopic studyconfirms the structure and phase purity of the sample. The M-H curve of YFeO3 shows a hysteresis loop, with a coercive field of 61 Oe and a residual magnetization of 0.516 emu/gm. Weak ferromagnetic nature of YFeO3 is attributed to the remnant magnetization value, which suggests that Fe +3 spins are slightly canted but not perfectly anti parallel. Room temperature P-E measurement of YFeO3 shows lossy ferroelectric nature of the sample.Positive Up Negative Down (PUND) measurementsdone on YFeO3 sample gives the trueswitchable polarization to be0.002 C/cm 2 .From the ln J versus ln E plot, the slope of the line is found to be 1.25, indicating Ohmic conduction in the sample. At 300 K, 57 Fe Mössbauerspectra of YFeO3 exhibit a single magnetic sextet, confirming the presence of a single Fe site and the absence of any magnetic impurities. The value of Isomer shift is0.37 mm/s, quadrupole splitting is found to be 0.01 mm/s, Line width (Г) = 0.47 mm/s and hyper fine magnetic field (Bhf ) of 49.8 T are being calculated from 57 Fe Mössbauer measurements.